PTP and LTP at a hippocampal mossy fiber-interneuron synapse - Alle, Henrik (The National Academy of Sciences, 2001)
The mossy fiber-CA3 pyramidal neuron synapse is a main component of the hippocampal trisynaptic circuitry. Recent studies, however, suggested that inhibitory interneurons are the major targets of the mossy fiber system. To study the regulation of mossy fiber-interneuron excitation, we examined unitary and compound excitatory postsynaptic currents in dentate gyrus basket cells, evoked by paired recording between granule and basket cells or extracellular stimulation of mossy fiber collaterals. The application of an associative high-frequency stimulation paradigm induced posttetanic potentiation (PTP) followed by homosynaptic long-term potentiation (LTP). Analysis of numbers of failures, coefficient of variation, and paired-pulse modulation indicated that both PTP and LTP were expressed presynaptically. The Ca(2+) chelator 1,2-bis(2-aminophenoxy)ethane-N,N,N′,N′-tetraacetic acid (BAPTA) did not affect PTP or LTP at a concentration of 10 mM but attenuated LTP at a concentration of 30 mM. Both forskolin, an adenylyl cyclase activator, and phorbolester diacetate, a protein kinase C stimulator, lead to a long-lasting increase in excitatory postsynaptic current amplitude. H-89, a protein kinase A inhibitor, and bisindolylmaleimide, a protein kinase C antagonist, reduced PTP, whereas only bisindolylmaleimide reduced LTP. These results may suggest a differential contribution of protein kinase A and C pathways to mossy fiber-interneuron plasticity. Interneuron PTP and LTP may provide mechanisms to maintain the balance between synaptic excitation of interneurons and that of principal neurons in the dentate gyrus-CA3 network.